Examination of anxiety levels of sportsmen with physical disabilities - (:unkn) unknown (My University, 2011)
The aim of this study is to determine state and trait anxiety levels of sportsmen with physical disabilities according to their sports branch and disability categories; and to determine whether they differ according to socio-demographic variables. The research included 120 sportsmen with physical disabilities, whose average ages were 30 ± 1.23 years. A socio-demographic data form and State Trait Anxiety Inventory (STAI) were used. Data were analyzed using SPSS (version 15.0). Both anxiety levels varied significantly (P<0.05) according to age and income level of the sample group and significant differences (p<0.05) were observed in educational level, income level and self-description in social life. No significant difference was observed in between either of the anxiety levels and participants' marital status, sports branch or disability category (p>0.05). In conclusion, while state anxiety levels of sportsmen with physical disabilities differ according to their age and income levels, their trait anxiety levels differ according to their income levels, personal characteristics like nervousness or irritability. It should be remembered that this state varies between individuals. Consequently, a high level of anxiety affects sportsmen negatively. Therefore, trainers and managers should demonstrate distinctive approaches to each sportsman, considering individual differences in their anxiety levels. © IDOSI Publications, 2011.
Keywords: Anxiety; Physical disability; State anxiety; Trait anxiety